Axis of convenience : Moscow, Beijing, and the new geopolitics - Lo, Bobo, 1959- (Brookings Institution Press, 2008)
Few relationships have been as misunderstood as the "strategic partnership" between Russia and China. Official rhetoric portrays it as the very model of international cooperation: Moscow and Beijing claim that ties are closer and warmer than at any time in history. In reality, however, the picture is highly ambiguous. While both sides are committed to multifaceted engagement, cooperation is complicated by historical suspicions, cultural prejudices, geopolitical rivalries, and competing priorities. For Russia, China is at once the focus of a genuine convergence of interests and the greatest.